Measurement of adult career decision motivation based on Self-Determination Theory and Classification of motivation profiles - Lee, YoungJu; Choi, HaeYoun (Korean Journal of Industrial and Organizational Psychology, 2020)
The purpose of this study was to validate the adult’s career decision motivation scale based on the self-determination theory, and examine the relation of motivation factors through cluster analysis. In Study 1, a sample of adults who have made career transitions participated, and scale items were selected based on interviews regarding their career decision making processes. In Study 2, selected items were rearranged into four motivation factors (external regulation, introjected regulation, identified regulation, intrinsic motivation) and the constructed scale was conducted on a sample of 240 adults with career transition experience. Data analyzed reported good validity and reliability of the 24-item model consisting of four motivational factors for each of the six behavioral items. Study 3 reports the results of a cluster analysis using the adult career decision motivations scale. Four meaningful clusters were identified and career decision motivation types were classified as ‘control motivated’, ‘poorly motivated’, ‘self-determined’, and ‘strongly motivated’. The strongly motivated cluster showed high levels of career adaptability(CA) and career satisfaction(CS), and the poorly motivated cluster showed low levels of CA and CS. The self-determined cluster had high CA, but there was no significant difference in CS from other clusters. Finally, how controlled motivation and autonomous motiavation could coexist and bring positive results in the cuareer decision making process of adults was discussed.